NATION-WIDE SURVEY ON THE USE OF THROMBOPOIETIN RECEPTOR AGONISTS (TPO-RA) FOR THE MANAGEMENT OF IMMUNE THROMBOCYTOPENIA IN CURRENT CLINICAL PRACTICE IN ITALY - Rodeghiero, Francesco; Napolitano, Mariasanta; Vianelli, Nicola; Ghiotto, Lisanna; Cantoni, Silvia; Carli, Giuseppe; Carpenedo, Monica; Carrai, Valentina; Consoli, Ugo; Giuffrida, Gaetano; et al. (Mediterranean Journal of Hematology and Infectious Diseases, 2023)
Background: Two thrombopoietin receptor agonists (TPO-RA), romiplostim and eltrombopag, are currently widely adopted as second-line ITP therapy even in absence of robust evidence on their comparative advantages over rituximab or splenectomy or their preferential use in some specific clinical contexts. Methods: An on-line survey was distributed between May 2021 and June 2021 to collect standardized information on the use of TPO-RA in Italy. Results: Eighty-eight hematologists from 79 centers completed the survey. Eighty-four percent would use TPO-RA earlier than formally indicated, without a preference for young or elderly in 82% of respondents. No clear preference for either romiplostim or eltrombopag was indicated. Seventy-two percent would use TPO-RA in young patients aiming at a complete response followed by tapering, a strategy considered by only 16% in the elderly. Switching between the two agents was considered appropriate in case of insufficient response or intolerance. Tapering schedule by reducing the dosage and prolonging the intervals between administrations was preferred by 73% of respondents. TPO-RA was considered a risk factor for thrombosis by only 35% and 94% would administer TPO-RA in elderly patients also in presence of other thrombotic risk factors. Thirty-three percent of respondents would withdraw TPO-RA in case of thrombosis. TPO-RA administration has been reported as being preferred over anti-CD20 or splenectomy by about half of participants due to the ongoing COVID-19 pandemic. Conclusions: Significant discrepancies in the use of TPO-RA emerged from the survey and participants would appreciate a consensus-based specific guidance on the practical use of TPO-RA.